RhoA G17E/Vav1 Signaling Induces Cancer Invasion via Matrix Metalloproteinase-9 in Gastric Cancer - Satoshi Nakamura MD; Masato Kitazawa MD, PhD; Yusuke Miyagawa MD, PhD; Makoto Koyama MD, PhD; Satoru Miyazaki MD; Nao Hondo MD; Futoshi Muranaka MD, PhD; Shigeo Tokumaru MD; Yuta Yamamoto MD, PhD; Takehito Ehara MD, PhD; Tomio Matsumura PhD; Michiko Takeoka PhD; et al. (Technology in Cancer Research & Treatment, 2023)
Background: RAS homolog family member A (RhoA), a member of the Rho family of small GTPases, and Vav1, a guanine nucleotide exchange factor for Rho family GTPases, have been reported to activate pathways related to the actin cytoskeleton and regulation of cell shape, attachment, and motility. The interaction between these molecules in lymphoma is involved in malignant signaling, but its function in epithelial malignancy is unknown. Here, we investigated the malignant signal of mutant RhoA in gastric cancer and demonstrated the potential of RhoA G17E/Vav1 as a therapeutic target for diffuse gastric cancer. Methods: The RhoA mutants R5W, G17E, and Y42C were retrovirally transduced into the gastric cancer cell line MKN74. The stably transduced cells were used for morphology, proliferation, and migration/invasion assays in vitro. MKN74 cells stably transduced with ectopic wild-type RhoA and mutant RhoA (G17E) were used in a peritoneal xenograft assay. Results: The RhoA mutations G17E and Y42C induced morphological changes in MKN74. G17E induced Vav1 expression at the mRNA and protein levels and promoted the migration and invasion of MKN74. An RNA interference assay of Vav1 revealed that RhoA G17E enhanced cancer cell invasion via Vav1. Furthermore, immunoprecipitation revealed that Vav1 and RhoA G17E specifically bind and function together through matrix metalloproteinase −9. In a peritoneal xenograft model of nude mice, RhoA G17E promoted peritoneal dissemination, whereas Vav1 knockdown suppressed it. Conclusion: Overall, our findings indicate that RhoA G17E is associated with Vav1 and promoted cancer invasion via matrix metalloproteinase −9 in gastric cancer cells. Thus, RhoA G17E/Vav1 signaling in diffuse gastric cancer may be a useful therapeutic target.